Determination of the Effect of Moringa oleifera Seed on the Rheological and Filtration Properties of Water Based Mud - Akintola, Sarah A.; Oloyede, Ifeoluwa; Emmanuel, Adeyeye (International Journal of Petroleum Technology, 2022)
A cost-effective and environmentally friendly biodegradable locally sourced alternative will be sought to reduce drilling fluid cost drilling operations. Moringa oleifera seed is a cheap, locally obtainable, and environmentally friendly additive. This study aims to determine the effect and suitability of locally processed Moringa oleifera seed powder (MSP) as an additive to improve the performance of water-based mud. The seeds were collected, prepared, and pulverized to a particle size of 75 microns. Varying concentrations (2.0, 4.0, 6.0, 8.0, and 10.0 g) of the MSP were used to treat a simple mud sample, and their properties were determined at varying temperatures (26°C, 40°C, 50°C, 60°C, 70°C) using American Petroleum Institute (API) standard procedures. Mud samples treated with Carboxymethyl cellulose (CMC) served as control. From the result, it was observed that the pH and the mud weight were not affected by MSP concentration. The mud sample plastic viscosity improved by 18% as MSP concentrations increased. The YP/PV ratios show an enhancement at all Moringa oleifera seed powder concentrations relative to the control mud except for the sharp decrease at 70°C. The test sample processed a greater fluid loss volume and filter cake thickness for all concentrations. The physical examination of the mud filter cake of the additive depicted that they have slippery, smooth, and soft mud cakes. The results elucidated MSP suitability in some traditional chemical materials in the oil and gas industry.